TYPES AND RISK FACTORS OF FIRST TIME STROKE: A SAUDI HOSPITAL- BASED STUDY (International Journal of Physiotherapy, 2019)
Background: The purpose of this study was to explore the stroke types and the risk factors of the first-time stroke in the holy city of Madinah Munawarah.Methods: A prospective hospital-based research study was carried out over the year of 2014. The patients with the diagnosis of the cerebrovascular accident were enrolled in the study. The details of patients’ history, demographic data, stroke type, and risk factors were collected.Results: First-time stroke were determined in 164 patients (91 male and 73 female) during the entire periods of this study with a mean age of 67.52 ± 2.31 years. The prevalence of types of stroke was ischaemic strokes in 133 patients(% 81.1), intercerebral hemorrhage in 24 patients (14.63%), and subarachnoid hemorrhage in one patient (0.6%). The most common risk factors recorded were hypertension (86.6%), diabetes mellitus (63.4%), and ischaemic heart disease (41.5%). There was no significant relationship between the frequency of ischaemic stroke and intercerebral hemorrhagestroke ( p> 0.05).Conclusion: The study indicates that hypertension, diabetes, and ischaemic heart disease are critical risk factors for developing stroke and fairly commensurate with the global reported risk factors. Further research is needed to investigate stroke patterns and other possible risk factors concurrently with Saudi national prevention programs.